PSYCHOLINGUISTIC PECULIARITIES IN UNDERSTANDING OF INDIRECT MEANING OF PROVERBS BY CHILDREN OF PRE-SCHOOL AGE - Kalmykova, Larysa; Kharchenko, Nataliia; Мysаn Іnna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The study reveales psycholinguistic peculiarities of understanding of indirect meaning of the proverbs of Ukrainian speaking pre-school children. The experiment took place on the basis of pre-school education establishments of Ukraine. Children were proposed to express themselves in order to find out how they understand given proverbs. If they had difficulties in meaning explication, so they were proposed some variants of proverbs interpretations, among which the first was correct (with indirect meaning) and the second with the direct meaning and the third with occasional associative meaning. The experiment proved such results: there are children with obvious intuitive language ability to feel the general meaning of proverbs. The proverb understanding is seen by child as complex cognitive task, which foresees decipherment of the common thought or conclusion, understanding its meaning (implication). That is why the proverbs cause problems among children.